Economic Packaging Design Using Custom Stamp - Haidar, Anisah (Universitas Mercu Buana, 2024)
This service activity took place in the RT 05 RW 04 area in the Palmerah sub-district area. This activity aims to help develop the business of UMKM players in the area by utilizing Custom Stamp to create economical packaging designs. This activity aims to strengthen branding and convey information to consumers about UMKM brands with a low budget but looks good. By using custom stamps, it can be used in various packaging media like boxes, paper, plastic, glass, mica and other packaging, so that the product looks much more attractive and strengthens the identity of the brand.